Dirty daddy : the chronicles of a family man turned filthy comedian - Saget, Bob (It Books, 2014)
Proudly embracing his dark and dirty side, the star of both Full House and America's Funniest Home Videos opens up about some of his personal experiences with life and death, his career and his reputation for sick humor.